Population structure and growth patterns of Diadema setosum (Echinodermata: Diadematidae) in the coastal ecosystems of Buru Island, Maluku, Indonesia - ASDAR BURHANUDDIN; SHARIFUDDIN B. ANDY OMAR; ELMI N. ZAINUDDIN; SYAFIUDDIN SYAFIUDDIN (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Burhanuddin A, Omar SBA, Zainuddin EN, Syafiuddin. 2025. Population structure and growth patterns of Diadema setosum (Echinodermata: Diadematidae) in the coastal ecosystems of Buru Island, Maluku, Indonesia. Biodiversitas 26: 2936-2945. Sea urchins (Echinoidea) are an important marine resource with economic and ecological value. Species such as Diadema setosum are consumed locally as a food source and are valuable in national and international markets. However, increasing demand has led to overexploitation, resulting in population declines. This research was carried out from February to July 2023 at two coastal locations, Jikumerasa Village in Buru District and Pasir Putih Village in South Buru District, Maluku Province, Indonesia. The aim was to analyze the growth patterns and condition indices of D. setosum. The method used is the line transect method, where sampling is carried out every month on a line transect that has five plots measuring 1x1 m. Data were compiled in tabular and graphical form using Microsoft Excel, regression equations were analyzed with data analysis software on regression software. Shell or test diameters of both male and female urchins ranged from 26.94-78.28, x?: 48.03±9.3mm SD, and body weights ranged from 11.39-249.37, x?: 72.18g±40.9 SD. The sea urchins from Pasir Putih station were greater than at Jikumerasa. The length-weight relationship (LWR) of D. setosum showed negative allometric growth in value equilibrium constant (b<3, p>0.05), with b-values ranging from 2.6763 to 2.7864. The Fulton’s condition factor (Kn) values ranged from 0.46 to 1.89 for males, 0.64 to 1.91 for females, and 0.43 to 1.91 for the combined population, indicating good overall health. Although more studies are needed to elucidate the effect of environmental conditions on echinoid sex determination, instances of skewed sex ratios may serve as indication for potential detrimental processes that may prevail in the environment. These findings contribute to a better understanding of the population structure and growth dynamics of D. setosum, which is crucial for guiding selective fishing methods, conservation strategies, and sustainable fisheries management.